1991
DOI: 10.1159/000200747
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Mucosal Interleukin-6 in Inflammatory Bowel Disease

Abstract: Interleukin-6, a cytokine produced by various cell types, has a major role in inflammatory and immunological reactions. To define its potential role in inflammatory bowel disease, its concentrations in endoscopic biopsy samples from patients with ulcerative colitis and Crohn’s disease were measured. The involved colonic mucosa from active disease was found to contain significantly larger amounts of interleukin-6 than that from inactive disease or normal controls. Colonic mucosal interleukin-6 levels correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 18 publications
2
56
0
Order By: Relevance
“…The IL-6 levels also correlated with the severity and extent of disease [3,7]. In other studies by our group [8] and others [9][10][11][12], increased levels of IL-6 mRNA and protein also have been demonstrated in colonic tissue obtained from patients with IBD. Furthermore, blocking of IL-6 actions with a monoclonal antibody against the IL-6 receptor (IL-6R) has been shown to attenuate inflammation in patients with CD [13], as well as animals with experimental colitis [14,15].…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…The IL-6 levels also correlated with the severity and extent of disease [3,7]. In other studies by our group [8] and others [9][10][11][12], increased levels of IL-6 mRNA and protein also have been demonstrated in colonic tissue obtained from patients with IBD. Furthermore, blocking of IL-6 actions with a monoclonal antibody against the IL-6 receptor (IL-6R) has been shown to attenuate inflammation in patients with CD [13], as well as animals with experimental colitis [14,15].…”
Section: Introductionmentioning
confidence: 53%
“…Furthermore, all these stimulants seem to act selectively on gp130, whereas IL-6R does not [36]. The above findings, together with the result of the high levels of inflammatory cytokines such as IL-6 or tumour necrosis factor-α during the active disease [8][9][10][11][12], suggest that such up-regulation of gp130 expression in response to these cytokines is not an in vitro event but a physiological phenomenon in vivo . Further studies will be needed to answer these questions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The pathogenesis of UC causing lung abnormalities is unkown, but both morphologic and developmental similarities exist between colonic and bronchial epithelium; both are derived from primitive gut and have columnar epithelia with goblet cells and submucosal mucus glands [14]. On the other hand, the activated inflammatory cells in bowel tissues are capable of producing a number of circulating cytokines such as interleukin 1, interleukin 2, interleukin 6 and tumour necrosis factor-a [15]. These and other mediators can regulate the endothelial cell adhesion molecules, alter white cell migration, increase the production of damaging reactive oxygen metabolites and induce damage of lung parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence after surgical resection is uncommon in UC (61). Both CD and UC are associated with the presence of activated macrophages and T cells; in addition, UC is associated with the presence of B cells in the inflamed intestine that tend to produce higher levels of IgG than the normal IgA (34,44,67,106,116 (16,98,137), (38,72,98), and tumor necrosis factor (TNF)-a (9,84,98). Furthermore, it has been suggested that CD may be a Thl-related disease, based on increased INF-'Y, IL-2, and IL-12 levels in the gut and undetectable levels of IL-4 and IL-5 (8,35,78,87,88).…”
Section: Inflammatory Bowel Disease In Humansmentioning
confidence: 99%